Development of social media and web 2.0 in the top hotel chains - Arturo Haro de Rosario; María del Mar Gálvez Rodríguez; María del Carmen Caba Pérez (Tourism & Management Studies)
The purpose of this paper is to analyze the use of Web 2.0 tools and social communication media in the hotel sector, to determine whether these technologies are a real solution for increasing the hotel sector’s visibility and enhancing that level of e-participation. Furthermore, it aims to examine what influences certain independent variables have in the greater use of these information and communication technologies. The web sites of the world's 50 largest hotel chains have been classified according to an index of visibility, considering the most important Web 2.0 tools and social networks. Results indicate a low use of Web 2.0 tools by hotel chains. However, their presence in social networks is more significant. The size and the age of the hotel chain influence the increased use of Web 2.0 and social communication media.